The Students Satisfaction, Student Loyalty, Competitive Advantage And Financial Sustainability On Private Universities In Surabaya - Dharmayanti, Diah; Semuel, Hatane; ., Devie (Advances in Social Sciences Research Journal, 2018)
Nowadays, the sustainability of private university is highly depending on several factors such as competitive advantage, students’ satisfaction and loyalty. The performance of those factors is affected by the financial ability of the university which generally comes from the students. The university management has to seriously put efforts to create value to the students. Value creation happens when the students get the benefits of the university’s quality service, university reputation, and the reasonable tuition fee. The students’ values are measured by the perception of the active students from the private universities that have been chosen as the respondents. The chosen private universities are Surabaya University (UBAYA), Ciputra University, Surabaya Higher School of Technology (STTS), Petra Christian University (UKP), Pelita Harapan University, and Widya Mandala University. The financial sustainability of private university is simultanuosly influenced by some variables which are competitive advantage, students’ satisfaction and loyalty, as well as students’ value creation. The result of the reseach shows that competitive advantage may create loyalty to the university, meanwhile the competitive advantage affects the financial sustainability of the university.